A visual grid to digitally record an Ayurvedic Prakriti assessment; a first step toward integrated electronic health records - Stranieri, A.; Henderson, K.B.; Sahama, T.; Perera, P.K.; Da Silva, J.L.; Pelonio, D.; Manjunath, S.S.; Raghavachar, D. (Journal of Traditional and Complementary Medicine, Elsevier, 2016)
In recent years, factors including globalization and economic growth in India and Sri Lanka have driven an important modernization of Ayurvedic Medicine, characterized by increases in evidence-based research and initiatives to standardize remedies and procedures...
Keywords: Ayurvedic medicine; Alternative medicine; Electronic health record; Health IT; Tridhosa